Sex determination through anthropometry of hand and foot in Thais - Romphothong, Metinee; Traithepchanapai, Pongpon (Chulalongkorn Medical Journal, 2023)
Background: Sex determination is one of the most important aspects in forensic anthropology for the identification of unknown remains, especially dismemberment or mass disaster cases in which mutilated or fragmented remains are usually discovered; it is difficult to establish the identity of a long deceased body. The acquired sex data are used by investigators for narrowing down ante-mortem data which can be derived from the relatives of the deceased before comparing to the postmortem data. Objective: This study aimed to estimate sex using hand and foot measurements by measuring the external parts of the bodies in a Thai population. Methods: Subjects were 100 Thai cadavers (50 males and 50 females), 20 - 60 years old, randomly selected. The 8 parameters from the hand and 3 parameters from the foot were measured using Mitutoyo digital calipers in SI units up to the accuracy of 3 decimals after breaking rigor mortis. Collected data were statistically analyzed using SPSS version 22. Cut-off values and accuracies were calculated for sex determinations. Results: Highly significant sex differences were found in hand parameters and foot parameters with males larger than females (P <0.001), except for the heel breadth; the hand and foot indexes were not significantly different between sexes. The cut-off values for sex determinations were derived from all of the measurements; values that are more than the cut-off point suggest male and less than the cut-off value suggest female sex. Hand length and 3rd finger in both sides showed the highest accuracies for sex determination and accuracies to differentiate between sexs were above 90%. In the foot, the highest accuracy to differentiate sex was the foot length, followed by the foot breadth with accuracy above 80%. Conclusion: Hand and foot parameters can be successfully applied for sex determination in Thais. Therefore, sex can be determined from the parameters of hands and feet with reasonable accuracy using the cut-off values.